Soft magnetic hysteresis in a dysprosium amide–alkene complex up to 100 kelvin - Jack Emerson-King; Gemma K. Gransbury; Benjamin E. Atkinson; William J. A. Blackmore; George F. S. Whitehead; Nicholas F. Chilton; David P. Mills (Nature, 2025)
Abstract Lanthanides have shown magnetic memory at both the atomic 1,2 and molecular 3,4 level. The magnetic remanence temperatures of lanthanide single-molecule magnets can surpass d -transition metal examples 5,6 , and since 2017, energy barriers to magnetic reversal ( U eff ) from 1,237(28) cm –1 to 1,631(25) cm –1 and open magnetic hysteresis loops between 40 K and 80 K have typically been achieved with axial dysprosium(III) bis(cyclopentadienyl) complexes 7–17 . It has been predicted that linear dysprosium(III) compounds could deliver greater m J (the projection of the total angular momentum, J , on a quantization axis labelled z ) state splitting and therefore higher U eff and hysteresis temperatures 18–21 , but as lanthanide bonding is predominantly ionic 22,23 , so far dysprosium bis(amide) complexes have shown highly bent geometries that promote fast magnetic reversal 24,25 . Here we report a dysprosium bis(amide)–alkene complex, [Dy{N(Si i Pr 3 )[Si( i Pr) 2 C(CH 3 )=CHCH 3 ]}{N(Si i Pr 3 )(Si i Pr 2 Et)}][Al{OC(CF 3 ) 3 } 4 ] ( 1-Dy ), that shows U eff = 1,843(11) cm –1 and slow closing of soft magnetic hysteresis loops up to 100 K. Calculations show that the U eff value for 1-Dy arises from the charge-dense amide ligands, with a pendant alkene taking a structural role to enforce a large N–Dy–N angle while imposing only a weak equatorial interaction. This leads to molecular spin dynamics up to 100 times slower than the current best single-molecule magnets above 90 K.